PENGEMBANGAN MEDIA INTERAKTIF BERBASIS WEB BAMBOOZLE DALAM MENINGKATKAN HASIL BELAJAR MATERI BILANGAN CACAH BESAR PELAJARAN MATEMATIKA KELAS IV SEKOLAH DASAR - Zulfa Ainul Hikmah; Arita Marini; Waluyo Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of developing Bamboozle web-based interactive media on improving learning outcomes in large number material in mathematics lessons for fourth grade elementary school students. This study used the research and development (R&D) method. The research design used an experiment with a quasi-experimental approach. The results of this study indicate that there is a significant effect of the development of web-based interactive media using Bamboozle on the learning outcomes of fourth-grade elementary school students in the subject of large whole numbers in mathematics.